Effect of Psidium guajava L. leaf extract on beef quality at different storage temperatures - Fazly Ann, Z.; Nik Sabri, N. N. N.; Rukayadi, Y. (Faculty of Food Science & Technology, UPM, 2022)
Psidium guajava L., or guava, has been widely reported as having antimicrobial activities against foodborne pathogens. However, the efficacy of P. guajava leaf extract at different storage temperatures has not been extensively explored. Therefore, the present work investigated the effect of antibacterial activity of P. guajava leaf extract on beef quality at different storage temperatures. Disc diffusion assay was performed on selected foodborne pathogens (Bacillus cereus ATCC33019, B. megaterium ATCC14581, B. pumilus ATCC14884, B. subtilis ATCC6633, Escherichia coli ATCC43895, Enterobacter aerogenes ATCC13048, Klebsiella pneumoniae ATCC13773, Pseudomonas aeruginosa ATCC9027, Salmonella Typhimurium ATCC14028, and Staphylococcus aureus ATCC29737) to evaluate the antibacterial activity of the ethanolic extract of P. guajava leaves. The results revealed inhibition zones ranging from 7.00 ± 0.00 to 10.00 ± 0.00 mm. MIC and MBC assays were conducted to assess the bacteriostatic and bactericidal effects of the leaf extract at a concentration range of 0.08 to 2.50 mg/mL, and > 5.00 mg/mL, respectively. The stability of the leaf extract was also measured at different temperatures and pH conditions by disc diffusion assay with the minimum inhibition zone of 7.00 ± 0.00 mm. The application of P. guajava leaf extract (0.05, 0.50, and 5.00%) on beef samples resulted in a continuous decrease in Total Plate Count during 14-day storage at refrigerated (4.0 ± 2.0°C) and freezing (-18.0 ± 2.0°C) temperatures. The results revealed that P. guajava leaf extract can effectively serve as a natural meat preservative to prolong the shelf life of the treated beef up to 14 days.